Dead certain - Stewart, Mariah (New York : Ballantine Books, 2004)
Relieved that her stalker is behind bars and that she can finally put her life back together, Amanda Crosby becomes caught up in a new nightmare when her business partner, Derek England, is found shot to death.
National College of Business and Arts
Keywords: Serial murders -- Fiction; Detective and mystery fiction